Season and No-Till Rice Crop Intensification Affect Soil Microbial Populations Involved in CH4 and N2O Emissions - Fernández-Scavino, Ana; Oreggioni, Daniela; Martínez-Pereyra, Andrea; Tarlera, Silvana; Terra, José A.; Irisarri, Pilar (Frontiers in Soil Science, 2022)
Rice is an important source of methane (CH4) whether other crops may be sources of nitrous oxide (N2O), both powerful greenhouse gases. In Uruguay, irrigated rice rotates with perennial pastures and allows high productivity and low environmental impact. A long-term experiment with contrasting rice rotations intensification alternatives, including rice-soybean and continuous rice, was recently installed in a Mollisol soil of temperate region of South America. To know if rotation systems influence soil microbial activity involved in CH4 and N2O emissions, the abundance and potential rate for gas production or consumption of microbial populations were measured during the rice crop season. CH4 was only emitted when rice was flooded and N2O emission was not detected. All rotational soils showed the highest rate for methanogenesis at tillering (30 days after rice emergence) while for methanotrophy the maximum rate was reached at flowering. The abundance of related genes also followed a seasonal pattern with highest densities of mcrA genes being observed at rice flowering whereas pmoA genes were more abundant in dry soils after rice harvest, regardless the rotation system. Differences were found mainly at tillering when soils with two consecutive summers under rice showed higher amounts of mcrA and pmoA gene copies. The potential denitrification rate was highest at tillering stage but the abundance of nirK and nirS genes was highest in winter. Regarding ammonium oxidation, bacterial amoA abundance was higher in winter while archaeal amoA gene were similar throughout the year. A strong influence of the rice growth stage was registered for most of the parameters measured in rice paddy soils in this no-till rice intensification experiment. However, differences among rotations begin to be observed mainly at tillering when the abundance of populations of the methane and nitrous oxide cycles seemed to respond to the rice intensification.